Validity and Reliability of the Persian Version of Parkinson's Disease Sleep Scale-2. (20th December 2021) - Joghataei, Mohammad Taghi; Fereshtehnejad, Seyed-Mohammad; Mehdizadeh, Maryam; Goudarzi, Sepideh; Habibi, Sayed Amir Hasan; Meimandi, Mahsa; Dehmiyani, Arian; Taghizadeh, Ghorban
Abstract : Objective . Sleep problems are nonmotor symptoms in Parkinson's disease that should be carefully evaluated for better management and treatment. Parkinson's Disease Sleep Scale (PDSS-2) is one of the most reliable tools for measuring sleep difficulties in people with Parkinson's disease. This study investigated the psychometric properties of the Persian version of PDSS-2. Methods . Four hundred and fifty-six people with Parkinson's disease with a mean age ±standard deviation of 60.7 ± 11.3 years were engaged in this study. Acceptability was assessed by floor and ceiling effects. Dimensionality was measured by exploratory factor analysis. The convergent validity of PDSS-2 with the Hospital Anxiety and Depression Scale (HADS) was assessed. Internal consistency and test-retest reliability were assessed with Cronbach's alpha and intraclass correlation coefficient (ICC), respectively. Results . No noticeable ceiling and floor effect was detected. The dimensionality analysis showed three factors. A high correlation was obtained between PDSS-2 and HADS (anxiety subscale). Excellent internal consistency with α  = 0.94, and good test-retest reliability with ICC = 0.89 were obtained. Conclusion . This study showed that the Persian version of Parkinson's Disease Sleep Scale has acceptable validity and reliability for measuring sleep disturbances in people with Parkinson's disease.